The Economic Benefits of Karimunjawa National Park - Ririn Irnawati; Domu Simbolon; Budy Wiryawan; Bambang Murdiyanto; Tri Wiji Nurani (Jurnal Perikanan dan Kelautan, 2012)
Karimunjawa National Park (KNP) inhabited mostly by fishery household, surrounds by 111.625 ha of waters. Protected area such as national park can essentially provide benefits for the survival of humans and other ecosystems. Economic valuation studies as one of the basic management becomes extremely important to be done to understand the extent of KNP provide benefit either directly or indirectly. These benefits should be assessed in economic value that management policy input can be done comprehensively. The objective of the research is to to assessing the economic benefit of KNP. Value of the economic benefits of KNP is Rp 53 Billion. Fishing activities contribute to the value of Rp. 30, 51 M (57.52%), tourism activities Rp. 11.28 M (21.26%) and ecosystem Rp. 11.26 M (21.22%).These value is benefit value and also opportunity cost if KNP ecosystem damage, the minimum economic loses to be borne by society.Keyword: economic valuation, Karimunjawa National Park